Additive manufacturing technology and its application in die manufacturing. Issue 2 (January 2021) - Hao, Botao; Lin, Guomin
Abstract: The increase of material manufacturing because of its direct forming characteristics and is widely used in aerospace, automobile manufacturing, mold manufacturing, medical equipment and other fields, this article, based on the characteristics and advantages of increasing material manufacturing, molding principle to increase material manufacturing technology and process as the research object, analyzes the material manufacturing technology on the accompanying cooling water mold, tire mold and the application of the large mold manufacturing.